The lost boys [videorecording (DVD)] - Feldman, Corey; Gertz, Jami; Haim, Corey, 1971-2010; Herrmann, Edward, 1943-2014; Hughes, Barnard, 1915-2006; Patric, Jason; Sutherland, Kiefer, 1966-; Wiest, Dianne (Warner Home Video, 2010)
When a string of mysterious deaths occur after they move to a coastal California town, teenagers Mike and Sam become convinced that their new home is overrun with vampires.